Mengukur kinerja keuangan perbankan syariah pada masa pandemi pasca turun SK/Edaran POJK No.18/POJK.03/2020 - Dewi, Nurmalisa Ismaya; Rofiuddin, Mohammad (Nur Science Institute, 2023)
This research aims to determine the influence of mudharabah financing variables, productive asset quality and bank operational efficiency on financial performance (ROA), as well as the influence of financing risk as a moderating variable. This type of research is quantitative research with a population at seven Islamic commercial banks registered with the Financial Services Authority (OJK), namely Bank BCA Syariah, Bank Syariah Bukopin, Bank Bank Muamalat Indonesia, Bank Panin Dubai Syariah, Bank Victoria Syariah, Bank Mega Syariah and Bank Jabar Banten Syariah in the pandemic era of 2020 and 2021 using quarterly data starting from the second quarter of 2020 to the third quarter of 2021. The method used in this research is Moderated Regression Analysis (MRA). This analysis shows that the mudharabah financing variable hurts return on assets. The quality of productive assets has a positive effect on return on assets. The operational efficiency ratio hurts return on assets. Non-performing finance can moderate mudharabah financing, productive asset quality, and the operational efficiency ratio of return on assets.